Pengaruh E-Modul Terintegrasi Etno-Stem melalui Project Based Learning (PJBL) terhadap Keterampilan Berpikir Kreatif Siswa pada Materi Zat dan Perubahannya - Sudarmi Sudarmi; Hadi Purwanto; Neng Shaolihat; Via Alissa (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
Creative thinking skills are fundamental competencies to be nurtured in 21st-century learning, especially within science education. One promising approach to developing these skills is the use of an Etno-STEM integrated E-Module implemented through the Project-Based Learning (PjBL) model. The Etno-STEM integration seeks to link local wisdom and culture with the domains of science, technology, engineering, and mathematics, thereby creating meaningful, contextualized learning experiences. This study aims to investigate the impact of implementing an Etno-STEM integrated E-Module through PjBL on students’ creative thinking skills. The research employed a quasi-experimental design with two classes: an experimental group using the Etno-STEM integrated E-Module and a control group using cooperative learning strategies. Research instruments comprised both test and non-test tools. The test instrument included objective-reasoned questions aligned with four creative thinking indicators—fluency, flexibility, originality, and elaboration—while the non-test instrument involved structured observation sheets to monitor learning implementation. Data analysis demonstrated that the Etno-STEM integrated E-Module using the PjBL model significantly improved students’ creative thinking skills compared to conventional approaches. This finding highlights the potential of combining local wisdom with innovative instructional models as an effective and culturally responsive strategy for advancing science learning aligned with 21st-century educational demands.